Electronic structure of the Ge/Si(1 0 5) hetero-interface: an ARPES and DFT study. (25th October 2018) - Sheverdyaeva, P M; Hogan, C; Sgarlata, A; Fazi, L; Fanfoni, M; Persichetti, L; Moras, P; Balzarotti, A
Abstract: We present a joint experimental and theoretical study of the electronic properties of the rebonded-step reconstructed Ge/Si(1 0 5) surface which is the main strained face found on Ge/Si(0 0 1) quantum dots and is considered a prototypical model system for surface strain relaxation in heteroepitaxial growth. Using a vicinal surface as a model system for obtaining a stable single-domain film structure with large terraces and rebonded-step surface termination, we realized an extended and ordered Ge/Si planar hetero-junction suitable for direct study with angle-resolved photoemission spectroscopy. At the coverage of four Ge monolayers photoemission spectroscopy reveals the presence of 2D surface and film bands displaying energy-momentum dispersion compatible with the 5 × 4 periodicity of the system. The good agreement between experiment and first-principles electronic structure calculations confirms the validity of the rebonded-step structural model. The direct observation of surface features within 1 eV below the valence band maximum corroborates previously reported analysis of the electronic and optical behavior of the Ge/Si hetero-interface.